Notch signaling genes: Myogenic DNA hypomethylation and 5-hydroxymethylcytosine - Terragni, Jolyon (Landes Bioscience, 2014)
Notch intercellular signaling is critical for diverse developmental pathways and for homeostasis in various types of stem cells and progenitor cells. Because Notch gene products need to be precisely regulated spatially and temporally, epigenetics is likely to help control expression of Notch signaling genes. Reduced representation bisulfite sequencing (RRBS) indicated significant hypomethylation in myoblasts, myotubes, and skeletal muscle vs. many nonmuscle samples at intragenic or intergenic regions of the following Notch receptor or ligand genes: NOTCH1, NOTCH2, JAG2, and DLL1. An enzymatic assay of sites in or near these genes revealed unusually high enrichment of 5-hydroxymethylcytosine (up to 81%) in skeletal muscle, heart, and cerebellum. Epigenetics studies and gene expression profiles suggest that hypomethylation and/or hydroxymethylation help control expression of these genes in heart, brain, myoblasts, myotubes, and within skeletal muscle myofibers. Such regulation could promote cell renewal, cell maintenance, homeostasis, and a poised state for repair of tissue damage.